2015
DOI: 10.1111/afe.12131
|View full text |Cite
|
Sign up to set email alerts
|

Plant-associatedBacillusspp. alter life-history traits of the specialist insectBrevicoryne brassicaeL.

Abstract: 1 Numerous soil-dwelling Bacillus species form mutualistic relationships with plants, in which the hosts derive an array of benefits, including the alteration of nutrient and chemical content. Despite such ubiquitous and intimate Bacillus-plant associations, the role of these bacteria in affecting the performance of specialist foliage-feeding insects is largely unknown. 2 We studied the effects of individual and mixed treatments of Bacillus cereus, Bacillus subtilis and Bacillus amyloliquefaciens on calabrese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 33 publications
1
18
1
Order By: Relevance
“…Hence, generalizing the effects of PGPR on aphid populations seems to be risky because responses are highly dependent on the set of involved species [47]. To our knowledge, the only study on B. amyloliquefaciens FZB42 and aphids had shown an alteration of the life traits of the aphid Brevicoryne brassicae on PGPR-treated calabrese plants [46], which is consistent with our observation of the decreased reproduction of A. pisum −E on PGPR-treated broad beans.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Hence, generalizing the effects of PGPR on aphid populations seems to be risky because responses are highly dependent on the set of involved species [47]. To our knowledge, the only study on B. amyloliquefaciens FZB42 and aphids had shown an alteration of the life traits of the aphid Brevicoryne brassicae on PGPR-treated calabrese plants [46], which is consistent with our observation of the decreased reproduction of A. pisum −E on PGPR-treated broad beans.…”
Section: Discussionsupporting
confidence: 87%
“…Several studies have reported various effects of PGPR on herbivorous insect development, including neutral [43,44], negative [17,[45][46][47], and positive effects [48,49]. Hence, generalizing the effects of PGPR on aphid populations seems to be risky because responses are highly dependent on the set of involved species [47].…”
Section: Discussionmentioning
confidence: 99%
“…This diverse community of bacteria in the leafhopper microbiome may contribute in several ways to the insect herbivores. The community also included endophyte bacteria (Gadhave & Gange, ). Some of the endophyte bacteria that we detected could function in plant protection against insects and diseases, including leafhoppers, representing an important function of the plant microbiome that interacts with the leafhopper populations; however, bacterial function is difficult to determine from 16S sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…This diverse community of bacteria in the leafhopper microbiome may contribute in several ways to the insect herbivores. The community also included endophyte bacteria (Gadhave & Gange, 2016 (Table S3). The bacterium Serratia marcescens is pathogenic to N. lugens (Niu, Liu, Li, & Guo, 2016).…”
Section: The Leafhopper Microbiomediversity and Functionmentioning
confidence: 99%
“…() who found that Bemisia tabaci nymphs developed faster and had higher survivorship after they fed on tomato plants that were pre‐inoculated with rhizobacteria. However, treatment of Calabrese (broccoli) with Bacillus species suppressed the growth and development of B. brassicae (Gadhave & Gange ). These studies suggest that the effects of PGPR treatment on insect pests can vary in relation to the feeding guild of insects.…”
Section: Introductionmentioning
confidence: 99%